The Changing Form of the Traditional Art of Gending Palegongan Lotring Style in Tanjung Benoa in the Global Era (Hindu Anthropology) - I Wayan Deddy Sumantra; Gede Bagus Wira Diputra (West Science Interdisciplinary Studies, 2026)
This study aims to analyze the changing forms of the traditional art of Gending Palegong and Lotring style in Tanjung Benoa in the era of globalization from the perspective of Hindu Anthropology. This study views traditional art not only as an aesthetic expression, but as an integral part of the religious system, cosmology, and yadnya practices in Balinese Hindu society. The study uses a qualitative approach with a cultural studies paradigm combined with a Hindu Anthropology framework, through a synchronic and diachronic approach. Data were obtained through participatory observation, in-depth interviews, documentation studies, and literature studies, then analyzed descriptively and interpretively using the theories of hegemony, power-knowledge, deconstruction, and globalization. The results show that changes occur in two main aspects, namely intrinsic and extrinsic elements. Intrinsic changes include the transformation of aesthetic concepts, repertoire, organology, and musical identity that have implications for shifting sacred and profane meanings in artistic practice. Extrinsic changes are evident in the dialectic between the preservation of classical canons as a noble heritage and the encouragement of innovation of the younger generation, which also influences the value of feeling and spiritual orientation in art. From a Hindu anthropological perspective, this dynamic reflects a negotiation process between art's function as a sacred offering (wali and bebali) and its function as a spectacle (balih-balihan) in a global and tourism context. This study concludes that the changes in Gending Palegong and Lotring style do not represent a degradation of tradition, but rather an adaptive cultural transformation in maintaining the sustainability of Hindu values amidst the currents of globalization. This phenomenon indicates a process of glocalization, in which the religious and cultural identity of the community is maintained through creative adaptation strategies.